Sustained Engagement to Create Resilient Communities: How a Collaborative Design Approach can Broker and Mobilise Practitioner–Participant Interaction. (October 2016) - McAra, Marianne
Abstract: When conducting research with young people, studies consistently cite the need to establish trust and rapport with participants. However, what frequently goes unreported is how to evolve these often highly fragile research relationships, and the subtle tensions and negotiations that can occur. In this article I reflect on my experience of collaborating with a group of young people, identified by their school teachers as vulnerable and at risk of falling through the educational net post compulsory schooling. Through a reflexive approach, this article explores how the use of a participatory filmmaking method enabled and sustained a research relationship between the participants and myself, outlining how trust and rapport gradually emerged. Drawing on relational ethics, I describe the catalysing and democratising role creativity played in gaining insights into group dynamics and the implicit strategies adopted by the young people in the search for social self‐empowerment.